Caracterização da pesca de tubarões e raias desembarcadas em Camocim: principal porto pesqueiro do Ceará - Basílio, Thiago Holanda (2011)
The fisheries landing port located in Camocim is the largest of Ceará State in respect to elasmobranch landings. However, qualitative and quantitative information about species landed in this site are lacking, as well as which fisheries are responsible for their capture. The goal of the present study was to investigate the artisanal and industrial fisheries fleet that land sharks and rays in Camocim. The landing data was obtained between January and December 2009. It was obtained in two ways: (1) biweekly by the author of this dissertation; and (2) daily by local data collectors. A total of 15 elasmobranch species belonging to five families were recorded. The total volume of elasmobranches landed was 6,782 specimens and 86,065 kg. Sharks captured by industrial fisheries and from Brazil’s north coast composed most of the landings. Sharks and rays were captured by 12 different kinds of fisheries. The nurse shark, Ginglymostoma cirratum, was one of the most landed species, even though it is considered threatened to extinction and its capture forbidden nationally. Environmental education campaigns promoting awareness of endangered elasmobranch species and law enforcement to avoid nurse shark captures are suggested.